Adaptive rule-based reservation CAC strategy for multimedia wireless networks - Deniz, DZ; Mohamed, NO (Acta Press, 2004)
An adaptive rule-based reservation call admission control (CAC) strategy is proposed. It is based on the guard channels strategy in which a number of channels are reserved and granted only to originating calls obeying a predefined rule. A multimedia wireless cell serving two types of customers; narrowband (n-type) which require b(n) channels and wideband (w-type) which require b(w) channels is studied. Handoff calls of both types also arrive in the wireless cell. In the proposed strategy, the channels in the wireless cell are divided into shared and guard channels. The shared channels are further divided into active and reserve channels. The active channels are used by originating calls of both types while the reserve channels are used by originating calls which obey a certain rule. Handoff calls can access all channels. It is found that when compared with the well known guard channel (GC) strategy.. the rule-based reservation (RR) strategy makes the system more fair to w-type calls. Handoff call dropping is also reduced when using RR strategy. These improvements are obtained at the cost of reduced server utilization and increased narrowband traffic blocking probability.
IASTED International Conference on Communication Systems and Networks -- SEP 01-03, 2004 -- Marbella, SPAIN
Keywords: adaptive CAC strategy; rule-based reservation; admission control; guard channels